Study of Residual Stress Distribution in Relation to Microstructure During Deep Cold Rolling of Al6061 - Kumar, Rakesh (My University, 2017)
The main objective of the present dissertation was to observe the residual stress distribution on the surface of the material during deep cold rolling. Deep cold rolling (DCR) is surface treatment technique and it is used to modify surface properties. During DCR, deformation takes place at the surface and sub surface of specimen which leads to surface finishing and increase its fatigue strength. The observed residual stresses were correlated with the microstructural features. The residual stress and microstructure characteristics were examined using X-ray diffraction and EBSD technique respectively. It was found that deep cold rolling leads to microstructure refinement and lowering of residual stress. The compressive residual stresses were higher on the sub-surface compared to top surface of the material. These stresses reduced with penetration depth at a particular deep rolled state. To confine such stress gradients, a 3-dimensional, elastic-plastic FE (finite element) model was developed. An agreement has been observed between the experimental and the simulated residual stress distributions.
Keywords: Aluminium Alloy, Deep Cold Rolling, Electron back Scattered Diffraction, Grazing Incidence X-ray Diffraction, Finite Element Method